If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+8)=2(4x-3)
We simplify the equation to the form, which is simple to understand
3(x+8)=2(4x-3)
Reorder the terms in parentheses
+(+3x+24)=2*(4x-3)
Remove unnecessary parentheses
+3x+24=+2+*(+4x-3+)
Reorder the terms in parentheses
+3x+24=+(+8x-6)
Remove unnecessary parentheses
+3x+24=+8x-6
We move all terms containing x to the left and all other terms to the right.
+3x-8x=-6-24
We simplify left and right side of the equation.
-5x=-30
We divide both sides of the equation by -5 to get x.
x=6
| x-8=80 | | n^2+4n-17=0 | | 4*a^2+b-2*a-b^2= | | 4(3x-2)+2(2x+1)=90 | | 3X+26=6 | | 3x^2-5x+m=0 | | 4(3x-2)+2(2x+1)=180 | | 9x=1-18 | | -7(x+6)-5=-47 | | 12-n=1.4 | | x^2-33*x+252=0 | | 3(w-6)=8w+2 | | b=x-my | | 5x+3=-67 | | 5(4y-8)-(4y+4)= | | 9x-2+2(x+3)=180 | | 1+x=-5+25 | | 5(3+5x)-2=8 | | 8-x=-2x-1 | | 21=5x+3x+4 | | 9y+7=14y+7 | | 81-4(9-3)= | | y-(250-75)=15 | | 32x(4x)=72 | | 2(x-4)+12(x-3)=180 | | |2x-3|=-7 | | 3.5x-2.1x=6.1 | | 10-4x=3x-4 | | y-1=m(x-(-2)) | | 3x-8+9x+2=90 | | -2x+y=15 | | 3.5x-2.11x=6.1 |